A Amazônia na dinâmica curricular do bacharelado de Relações Internacionais (RI) da Universidade Federal de Roraima (UFRR) - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
The present study is part of Research Line 3: Education and Praxis of the Educator Facing the Amazonian Challenges as it discusses, what contents about the Amazon are present in the curriculum in International Relations, in this way it intends collaborate with the training of teachers in higher education. The general objective of the study is to analyze how the Amazon is worked in the curricular dynamics of the Bachelor of International Relations (IR) at the Federal University of Roraima (UFRR), this intent unfolds in the following specific objectives: 1). To investigate the assumptions of historical-critical theory in higher education and in the curriculum; two). To know the concepts of higher education in the world and in Brazil, as well as the insertion of the International Relations course in the Amazon; and 3). Elucidate the curricular dynamics of the International Relations course at UFRR, through Amazonian themes present in teaching, research and extension. To this end, our theoretical- methodological support was anchored in historical-critical theory and its consequent curricular theory, in addition to training studies in International Relations, as well as authors who debate the Brazilian Amazon. In methodological terms, we use documentary and primary sources analyzed in a qualitative way, among the analyzed documents are the National Curriculum Guidelines (DCNs) of the Bachelor of International Relations, the Institutional Development Plan (PDI) of UFRR and the Pedagogical Project the UFRR IR Course (PPC), in addition to extracting information from the course website about current monographs and extension projects; for the collection of primary data, three interviews were conducted, one with the course coordinator and two with teachers who had already taught mandatory subjects directly related to the Amazon, a Discussion Group was also held with the finalist students of 2019. Among the results we highlight that the course on International Relations (IR) at the Federal University of Roraima (UFRR), within the scope of teaching, conducts a direct dialogue on the Amazon expressed in three disciplines that address the interaction between the Amazon and International Relations, as well as indirectly this content it is also worked in other subjects during the course. From the monographic works defended, in the research sphere, the themes of migration, refuge and displacement stand out. In turn, most extension projects are related to the humanitarian crisis resulting from Venezuelan migration. It is concluded that Venezuelan migration has reoriented the curriculum dynamics and that despite the individual efforts of the course teachers in teaching, research and extension, there is no work organized collectively and subsidized in a previous diagnosis of local needs in order to prioritize contents and responses to Roraima and Amazonian society. However, we would like to emphasize that such difficulties do not depend only on the political will of professors and students to make the UFRR IR course a reference pole in the knowledge about the Brazilian Amazon in the area of international relations, there are structural difficulties that public university goes through, either through the strategies of social delegitimation or by the constant reduction of funding perpetrated by the new tax regime, approved in 2016.
Keywords: Ensino superior - Roraima; Universidades e faculdades - Currículos; CIENCIAS HUMANAS: EDUCACAO; Amazônia; Dinâmica curricular; Ensino superior; Formação em Relações Internacionais